Optimalisasi Fungsi Masjid Sebagai Pusat Dakwah dan Pendidikan Umat:Pengalaman Kegiatan KKN di Masjid Rohmat Bakipandeyan - Bayu, Aji; Budiriyanto, Anis; Novitasari, Shovi; Lailatus Sa adah, Falihah; Nu aim, Abdullah; Ayisa Sahidah, Asma; Nur Azizah, Fahriska; Nur Azizah, Fikriyah (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The Kuliah Kerja Nyata (Community Service Program) is one of the concrete implementations of Indonesia’s “Tri Dharma Perguruan Tinggi,” particularly the pillar of community service. This article describes a community engagement experience carried out by students of STIM Surakarta at Masjid Rohmat Bakipandeyan. The main focus of the program was optimizing the mosque’s function as a center of da‘wah (Islamic preaching) and ta‘līm (religious education) for both adult congregants and children of the TPA (Qur’anic Learning Center). Using a participatory and reflective approach, the program involved seven students, sixty active congregants, and thirty TPA students. The results show improved participation in religious activities and enhanced motivation among the TPA students. The study further highlights the strategic role of the mo sque as a community-based institution for Islamic education and moral development.